Chart review across EU5 in MM post-ASCT patients. (11th July 2018) - Ashcroft, John; Judge, Davneet; Dhanasiri, Sujith; Taylor-Stokes, Gavin; Middleton, Chloe
Aim: To understand the current treatment patterns, clinical outcomes and healthcare resource utilization–associated costs for multiple myeloma patients, post autologous stem cell transplant (ASCT) across Europe.Patients & methods: Medical records were used to abstract data for 337 multiple myeloma patients who had received ASCT.Results: Following ASCT, 7% received maintenance therapy prior to progression. Lenalidomide was the most frequently prescribed maintenance, second- and third-line therapy. Monthly resource use was considerably lower in patients who received maintenance therapy (€638.14 vs €1001.74). Median time to progression was longer for patients who had received maintenance therapy.Conclusion: The study highlights the diversity in current treatment patterns post-ASCT. Results suggest patients who receive maintenance therapy have a prolonged remission period, and as a result their associated healthcare resource utilization is spread across the treatment pathway.